2019
DOI: 10.2196/formative.9995
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of an Animated Electronic Health Video to Increase Knowledge of Post- and Pre-Exposure Prophylaxis for HIV Among African American Women: Nationwide Cross-Sectional Survey

Abstract: Background Despite renewed focus on biomedical prevention strategies since the publication of several clinical trials highlighting the efficacy of pre-exposure prophylaxis (PrEP), knowledge of postexposure prophylaxis (PEP) and PrEP continues to remain scarce among women, especially among African American women who are disproportionally affected by HIV. In an effort to address this barrier and encourage uptake of PEP and PrEP, an electronic health (eHealth) video was created using an entertainment… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 53 publications
(81 reference statements)
0
52
0
3
Order By: Relevance
“…In this study, among the staff recruited from community-based HIV/AIDS service organizations located in South Carolina and Texas, more than half used email and text message to communicate with their clients. In addition to the vast number of US adults who are online, another contributing factor to this study's findings is the fact that most people living with HIV are men who have sex with men who, studies have shown, go online for health information and social networking [ 10 ]. Additionally, the fact that most of the community-based HIV/AIDS service organization staff who participated in the study were completely or very confident that electronically shared information was protected and private is also a contributing factor to electronic communication with clients, and interest in eHealth communication with clients in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, among the staff recruited from community-based HIV/AIDS service organizations located in South Carolina and Texas, more than half used email and text message to communicate with their clients. In addition to the vast number of US adults who are online, another contributing factor to this study's findings is the fact that most people living with HIV are men who have sex with men who, studies have shown, go online for health information and social networking [ 10 ]. Additionally, the fact that most of the community-based HIV/AIDS service organization staff who participated in the study were completely or very confident that electronically shared information was protected and private is also a contributing factor to electronic communication with clients, and interest in eHealth communication with clients in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Voiceover actors included undergraduate students with backgrounds in theater performance from the University of Pennsylvania. The cast of animated characters was meant to represent people from different cultural backgrounds through dress, gender, ethnicity, and age to tailor the video to a diverse population (Bond & Ramos, 2019). Previous research has found that culturally tailored eHealth videos could be used to increase awareness of HIV prevention methods, since the viewers may identify with the characters of the stories and lessen their resistance to the health message (Bond & Ramos, 2019).…”
Section: Intervention Development Processmentioning
confidence: 99%
“…Electronic delivery of HIV prevention interventions enables broad dissemination of knowledge and requires fewer resources than in-person delivery, while yielding significant effects on sexual health and health behavior [ 7 ]. In studies conducted with women, including studies with Black and Latinx women specifically, electronically-delivered HIV prevention interventions have been highly acceptable and similar or superior in efficacy than interventions delivered in person [ 8 14 ]. To date, few studies have evaluated electronically-delivered interventions that focus particularly on PrEP education among women [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In studies conducted with women, including studies with Black and Latinx women specifically, electronically-delivered HIV prevention interventions have been highly acceptable and similar or superior in efficacy than interventions delivered in person [ 8 14 ]. To date, few studies have evaluated electronically-delivered interventions that focus particularly on PrEP education among women [ 8 , 9 ]. One study evaluated a brief web-based educational video about PrEP among a community-based sample of 116 Black women and found the video to be highly acceptable [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation